Big Data - Anil Maheshwari (McGrawHill, 2017)
This book is meant for students, as well as executives, who wish to take advantage of emerging opportunities in Big Data. It provides an intuition of the wholeness of the field in a simple language, free from jargon and code. All the essential Big Data technology tools and platforms such as Hadoop, MapReduce, Spark, and NoSql are discussed. The short chapters make it easy to quickly understand the key concepts. A complete case study of developing a Big Data application is included.